Preliminary findings: Preferences of right-handed people for food images oriented to the left vs. right side. (April 2022) - Shibuya, Kenichi; Kasuga, Rina; Sato, Naoto; Santa, Risa; Homma, Chihiro; Miyamoto, Mana
Highlights: It was examined that people have preference for right-facing-objects when it comes to food, but have no preferences when it comes to objects including landscapes. Japanese young females who are right-handed and right-to-left readers tended to prefer the left-tilted pictures of food. There was no significant difference in preferences for right- and left-tilted pictures of objects that could not be grasped, such as cars and landscapes. People may prefer images in which foods are oriented in a manner that would make them easy to grasp and bring to the mouth. Abstract: It is well known that aesthetic preferences regarding lateral biases are influenced by left/right reading habits, as people who read text left-to-right have been shown to prefer left-to-right oriented images. However, preferences regarding objects that are more strongly associated with actual objects in daily life and the movements used to interact with such objects are less well understood. Images of foods may trigger cognitive pathways related to grasping and bringing food to the mouth, which may influence preferences regarding such images. Participants were presented with successive pairs of food images and asked to choose the preferred image. They were also presented with pairs of object images that are not easily graspable, such as landscapes; these pairs were differentiated in the same way as the food images. Each pair consisted of the same images but at a different angle. Participants preferred images of foods that were oriented in a direction that made it easier to grasp and bring to the mouth with the right hand (p < 0.001). In conditions involving landscape images that were difficult to grasp, there were no significant differences in participants' preferences (p > 0.05). From this study's results, it can be concluded that the orientation with which foods are presented influences preferences, and that people may prefer images in which foods are oriented in a manner that makes them easy to grasp and bring to the mouth.